The impact of social networks and APOE ε4 on dementia among older adults: tests of possible interactions. (3rd March 2020) - Wu, Jing; Hasselgren, Caroline; Zettergren, Anna; Zetterberg, Henrik; Blennow, Kaj; Skoog, Ingmar; Halleröd, Björn
Abstract: Objectives: Emerging evidence suggests that social networks may protect against the development of dementia among older adults. In this study we analysed the association between social networks, the apolipoprotein E ( APOE ) ε4 allele, and dementia. We also investigated whether there were gender-specific patterns in this respect. Method: The analyses used population-based longitudinal data from Gothenburg, Sweden: the H70 Birth Cohort Study and the Prospective Population Study on Women (PPSW). A total of 580 individuals born in 1930 underwent semi-structured neuropsychiatric examinations in 2000–2001. Follow-up examinations were carried out in 2005–2006 and 2009–2010. The timing of dementia onset was analysed using Cox proportional hazards regression. Results: The presence of the APOE ε4 allele affected the risk of developing dementia in both genders. Among women, distant social networks had a protective effect on dementia, while among men the significant associations between close social networks and dementia did not remain after controlling for covariates. Significant interactions between social networks and the APOE ε4 allele were not found. Conclusion: Strong social networks do not seem to moderate the increased risk of dementia implied by the APOE ε4 allele. Nevertheless, our results underline the importance of strong social networks in postponing dementia onset and indicate that their impact may differ among men and women.